Cesare Pavese nei sudi rapporti con la letteratura americana - Balzan, Rosa Anna Maria (My University, 2014)
Cesare Pavese has been studied in many critical essays, as a prose writer and a poet, as well as a critic of American Literature. In all the critical studies, Pavese has been presented as one of the leading figures of 20th century Italian Literature and the various critics have, up till now, underlined, more or less emphatically the fact that American Literature has deeply influenced Pavese and, through him, contemporary Italian Literature. Pavese has been studied in his relationship with American Literature chiefly by three groups of critics. One group, after making a superficial survey of his works, has drawn the conclusion, without any real proof, that American Literature has influenced Pavese. Another group has said that Pavese is a completely original writer, whilst declaring, at the same time, that he was definitely influence' by American Literature, thus inevitably falling in several and eeri contradictions. Vet another group has made false and unfounded accusations and has come to the conclusion that Pavese has been influenced not only By the American authors he studied, but also by their American critics. The aim of the present research work is to clarify the ambiguous judgments and to dispel the false accusations made against Pavese. The present work shows through a carerul reading of ell translations, essays, prefaces, articles that Pavese wrote an American Literature, through a close examination of Italian criticism and of the major American critical works, that Pavese was neither influenced by American authors nor by American critics. The present work shows that Pavese has been, on the contrary, a profound and original critic of American Literature; his examination of the various linguistic techniques, used by American authors, and their intersction, makes Pavese the precursor of modern Struc^uriilism. The first chapter of this dissertation Pavese and contemporary Italian and European Literature gives a general survey of Italian and European Literature from the end of 19th century, when new literary ideas were born, to the beginning of the 20th century, when these ideas gave their first results; it continues with an examination of the period between Wars and it concluded with the second post-war period. The second chapter Pavese and the critical studies on American Literature, discusses American cultural "landing" in Europe; it analyses the first generation of critics of American Literature : D.H. Lawrence S E. Cecchi; it brings to the attention of the reader the definite change in the interpretation of American Literature through A. Gremeci and G. Pintor; it presents the second generation of critics of American Literature : E. Vittorlni and C. Paveae. The third chapter Pavese'a encounter with two Romantic writers ; Welt Whitman and Herman Melville gives a concise historical ind-Trterer7-p8n5Faris-oF^hs~pHiiod-Tn-liihrch American Romanticism started; it analyses Paveae's critical studies on W. Whitman and H. Melville and it presents a brief survey of American criticism on these authors. The fourth chapter Pavese's encounter with two Realist writers ; Sinclair Lewis and Sherwood Anderson, gives a concise historical and literary panorama, of the period" in which American Realism started; it outlines American Realism : before tne First World lilar, between liters, and after the Second World War; it analyses Pavese's critical studies an S. Lewis and Sh. Anderson and it presents a brief survey of American criticism on these authors. The Conclusion examines the various ambiguous and superficial judgments and it dispels the false accusations made against Psveae; it ends by showing that Peveae has been an original and profound critic and tiv.t he has not been influenced by American authors, neither in content nor in style. American Realism started; it outlines American Resliam : Dafore the First World War, between Wars, end after the Second World War; it analyses Pavese'a critical studies on 5. Lewis and 5h. Anderson and it presentg a brief survey of American criticism on these authors. The Conclusion examines the various ambiguous end superficial judgments and it dispels the false accusations made against Pavese; it ends by showing that Pavsse has been an original anti profound critic and that he has not been influenced by American authors, neither in content nor in style.
Thesis (M.A.)--University of the Witwatersrand, Faculty of Arts, 1976.